Регіональна модель профілактики йодного дефіциту - Зелінська, Н. Б.; Труш, О. А.; Маменко, М. Є.; Бєлих, Н. А. (Clinical Endocrinology and Endocrine Surgery, 2009)
The article deals with some mechanisms of a regional iodine deficiency prevention program creation. The WHO/ICCIDD/UNICEF recommendations were adopted to the local conditions. The Luhansk regional model for IDD control program was described. The basic areas of the program implementation and the organizations involved to the process were detected.